SpyGlass DS-Directed Radiofrequency Ablation With Double Biliary Metal Stent Placement for Managing Recurrent Obstructive Jaundice Secondary to Castleman Disease: A Case Report of a Rare Disease - Chen, Yongjin; Fu, Chang; Chen, Junhong; Pan, Weicong; Fu, Yu; Liu, Kai (Frontiers in Surgery, 2022)
Castleman disease (CD) rarely presents with obstructive jaundice, which poses a diagnostic and therapeutic challenge to the management of the disease. A 40-year-old man was referred to our hospital for emergent management of upper abdominal pain. An abdominal mass was removed, and the postoperative pathology showed retroperitoneum CD, which was subsequently managed by adjuvant therapy of combination chemotherapy and steroids. One month later, a biliary metal stent was placed due to the presentation of obstructive jaundice. After approximately 3 months, the patient experienced another episode of obstructive jaundice, and SpyGlass DS cholangioscopy (Boston Scientific, Natick, Mass, USA) was performed via the biliary track for biopsy, which pathologically showed biliary malignancies. Radiofrequency ablation was performed with a probe (EMcision, Montreal, Canada), and another uncovered metal stent was placed within the existing metal stent. No stent occlusion occurred during a 6-month follow-up period. In conclusion, CD rarely presents with obstructive jaundice, and a combination of radiofrequency ablation with metal stent implantation under cholangioscopy can prolong the stent patency time and the survival time of patients.